1999
DOI: 10.1001/archpsyc.56.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Declarative and Procedural Memory Functioning in Abstinent Cocaine Abusers

Abstract: This study documented a lasting detrimental effect on a sensitive nonverbal declarative memory task in cocaine-dependent subjects following abstinence of 45 days. In contrast, abstinence from cocaine during this 45-day period was associated with sustained improvement on a motor learning test in the cocaine abusers relative to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 16 publications
6
48
0
10
Order By: Relevance
“…Physiologic studies have shown decreased metabolism in the orbitofrontal cortex (Volkow et al, 1988) and increased cerebrovascular resistance in the arteries that supply the PFC (Herning et al, 1999). Some reports of neuropsychological testing in cocaine using subjects have identified decreased performance on tests that require the support of prefrontal structures (Ardila et al, 1991;Berry et al, 1993;Beatty et al, 1995;van Gorp et al, 1999;Di Sclafani et al, 2002). A relationship between the amount of cocaine consumed and neuropsychological deficits in attention, planning, mental flexibility, executive function, and psychomotor function have been reported (Bolla et al, 1998(Bolla et al, , 1999(Bolla et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic studies have shown decreased metabolism in the orbitofrontal cortex (Volkow et al, 1988) and increased cerebrovascular resistance in the arteries that supply the PFC (Herning et al, 1999). Some reports of neuropsychological testing in cocaine using subjects have identified decreased performance on tests that require the support of prefrontal structures (Ardila et al, 1991;Berry et al, 1993;Beatty et al, 1995;van Gorp et al, 1999;Di Sclafani et al, 2002). A relationship between the amount of cocaine consumed and neuropsychological deficits in attention, planning, mental flexibility, executive function, and psychomotor function have been reported (Bolla et al, 1998(Bolla et al, , 1999(Bolla et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Only one other study has directly examined both basal ganglia-and medial-temporal lobemediated learning in cocaine abusers (van Gorp et al, 1999); this study used a motoric procedural learning task and two declarative learning tasks to measure these respective learning systems. Results indicated that within 72 hours of their most recent cocaine use (confirmed by urine toxicology), cocaine users exhibited faster learning of motor tracking (Pursuit Rotor task; Spreen & Strauss, 1991), weaker performance on a visual learning test (Rey-Osterreith Complex Figure task; Spreen & Strauss, 1991), and similar performance on a verbal learning task (California Verbal Learning Test; Delis et al, 1987), relative to age-matched healthy control participants.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found no alterations using classical measures of verbal memory based on word lists [31,33,34]. These data should not be interpreted as indicative of the absence of dysfunctions in the memory subsystems in this population, since a broader mnesic assessment [35], including the strategic components of memory [36].…”
Section: Discussionmentioning
confidence: 65%